Historical Development Stages of the Scholarly and Religious Center Najaf - Baghirov, Samid (Scholarya Demo Journal of Ruby, 2018)
The history of scholarly and religious center in Iraqi city of Najaf dates back to thousand years. The city rose to its florescence after Sheykhut-Taifa at-Tusito Najaf’s arrival. He started a scholarly and religious center here and accelerated ijtihad process with the methods of teaching which attracted the scholars from other regions.The center faced hundrd years of stagnation after Sheikh Tusi until the time of Ibni Idriss Hilli, later, the state support for the Buwayhids and Safavids expanded the activities of the center. The educational texts of the center were developed in the 16thcentury, however, it experienced another stage of stagnation. This was due to the proliferation of Akhbaris in Najaf. In the 18th century, the Usuli scholars surpassed the Akhbaris and created a scholarly and religious doctrine that accelerated the process of ijtihad with new rational rules.